Extended maximum boost control scheme based on single-phase modulator for three-phase Z-source inverter - Sabeur, N.; Mekhilef, S.; Masoud, Ammar (The Institution of Engineering and Technology, 2016)
This study proposes a new control method for Z-source inverter (ZSI) - called the one-dimension ZSI (ODZSI) - based on the single-phase modulator technique. The notable feature of the proposed control compared with the space-vector modulation strategy is its reduced computational processing time, which is attractive for digital implementation. Compared with the maximum boost control (MBC), which uses carrier-based pulse width modulation control methods, the proposed algorithm enhances the output voltage and current quality. In this study, the results of MBC are compared with those obtained with a single-phase modulator for three-phase ZSI showing its advantage for improving the line output current and voltage total harmonic distortion. The obtained simulation and hardware results ensure the feasibility and validate the performance of the ODZSI modulation method applied to each phase. The proposed method is easier for digital implementation with less computation, and will be beneficial for further industrial applications of ZSIs. The simulation results are carried out using MATLAB/Simulink, and the hardware performance are provided and discussed.